2021
DOI: 10.1108/ecam-06-2021-0539
|View full text |Cite
|
Sign up to set email alerts
|

Safety climate and occupational safety behaviours: the mediating role of psychological ownership among construction professionals

Abstract: PurposeEncouraging employee's safety behaviour remains a challenge in the construction industry from developing countries. Several studies have examined the nexus between safety climate and safety behaviour. This paper investigates the psychological ownership as a mediator in the relationship between safety climate and occupational safety behaviours among construction professionals in Ghana.Design/methodology/approachA cross-sectional design was used for the study. Two hundred and eighty-two respondents (282) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 90 publications
0
4
0
Order By: Relevance
“…From an individual point of view, instead, a sense of autonomy, competence, and personal belief in the importance of safety also play a role in fostering psychological ownership for safety (Curcuruto et al, 2020). Several studies have shown that employees with a strong sense of psychological ownership for safety are more likely to engage in safety-related behaviors, due to the belief that their actions can make a difference in maintaining a safe work environment (Novieto, 2023;Y. Zhang et al, 2021;Z.…”
Section: Safety Ownership Affective Commitment and Performancementioning
confidence: 99%
“…From an individual point of view, instead, a sense of autonomy, competence, and personal belief in the importance of safety also play a role in fostering psychological ownership for safety (Curcuruto et al, 2020). Several studies have shown that employees with a strong sense of psychological ownership for safety are more likely to engage in safety-related behaviors, due to the belief that their actions can make a difference in maintaining a safe work environment (Novieto, 2023;Y. Zhang et al, 2021;Z.…”
Section: Safety Ownership Affective Commitment and Performancementioning
confidence: 99%
“…Therefore, with in-depth study, the burst of the keyword "mediating role" is logical. Future research should integrate with existing research clusters, such as safety climate [87][88][89] and knowledge management [90], to conduct more objective empirical research on the mechanism of construction project organisation. The mediating role of project success factors when it comes to different types of leadership will become a research hotspot in the future [91][92][93].…”
Section: Future Reserch Trendsmentioning
confidence: 99%
“…One approach to this is through the psychological contract (PC), an important perspective that has become an increasingly popular research topic in this journal in particular over the years, including in employee career expectations (Dainty et al, 2000), the expectations of project managers (Dainty et al, 2004), improved organizational innovations (Egbu, 2004), the motivation of workers (Liu et al, 2007), knowledge sharing (Wang and Shi, 2019), the efficacy of trust , construction manager burnout (Franz et al, 2021), and renegotiating relationships within the PPP scheme (Feng et al, 2022). In terms of construction safety, studies involving PC are replete, with major contributions by Newaz (2018), Newaz et al (2016aNewaz et al ( , 2016bNewaz et al ( , 2018Newaz et al ( , 2019aNewaz et al ( , 2019bNewaz et al ( , 2019cNewaz et al ( , 2020aNewaz et al ( , 2020bNewaz et al ( , 2021aNewaz et al ( , 2021b, Novieto (2021) and many others.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of construction safety, studies involving PC are replete, with major contributions by Newaz (2018), Newaz et al. (2016a, b, 2018, 2019a, b, c, 2020a, b, 2021a, b), Novieto (2021) and many others.…”
Section: Introductionmentioning
confidence: 99%